Factors Affecting Innovations Development in Priority Industries of a Region - Soboleva, Ol’ga Nikolaevna; Burtseva, Tat’jana Alekseevna; Nabokih, Aleksej Anatol’evich; Shpengler, Anna Vladimirovna (International Review of Management and Marketing, 2016)
In the era of world economy globalization the success of a country or a region is based upon constant innovations updating aimed at achieving maximum productivity, competitiveness, development of human capital. In this respect a wide use of innovations is the most efficient and effective means of solving social and economic problems also in agricultural sector. Thus the priority is to identify the factors holding back the development of innovation in agricultural sector as well as the factors contributing to their development. The statistical data used in identification of these factors are not always reliable and sufficient, it is also necessary to apply other means of obtaining and processing of information via discriminant, cluster and factor analysis. Keywords: Innovation, agro-industrial complex, branches of agriculture. JEL Classifications: Q11, Q13, O31